Novel compound heterozygous variants in EMC1 associated with global developmental delay: a lesson from a non-silent synonymous exonic mutation - Wang, Ge; Wang, Yanli; Gao, Chao; Xie, Wanqin (Frontiers in Molecular Neuroscience, 2023)
Background: The endoplasmic reticulum-membrane protein complex (EMC) as a molecular chaperone is required for the proper synthesis, folding and traffic of several transmembrane proteins. Variants in the subunit 1 of EMC (EMC1) have been implicated in neurodevelopmental disorders. Methods: Whole exome sequencing (WES) with Sanger sequencing validation was performed for a Chinese family, including the proband (a 4-year-old girl who displayed global developmental delay, severe hypotonia and visual impairment), her affected younger sister and her non-consanguineous parents. RT-PCR assay and Sanger sequencing were used to detect abnormal RNA splicing. Results: Novel compound heterozygous variants in EMC1, including the maternally inherited chr1:19566812_1956800delinsATTCTACTT[hg19];NM_015047.3: c.765_777delinsATTCTACTT;p.(Leu256fsTer10) and the paternally inherited chr1:19549890G>A[hg19];NM_015047.3:c.2376G>A;p.(Val792=) are identified in the proband and her affected sister. RT-PCR assay followed by Sanger sequencing reveals that the c.2376G>A variant leads to aberrant splicing, with retention of intron 19 (561bp) in the mature mRNA, which is presumed to introduce a premature translational termination codon (p.(Val792fsTer31)). Conclusion: Novel compound heterozygous variants in EMC1 have been identified in individuals with global developmental delay. Non-silent synonymous mutations should be kept in mind in genetic analysis.